A method for increasing the compatibilization of incompatible biodegradable polymer blends
By introducing carbon black into the polylactic acid and polybutylene succinate blending system and using Pickering emulsion template and melt blending technology, the thermodynamic incompatibility between polylactic acid and polybutylene succinate is solved. The problem of insufficient mechanical properties of blends significantly improves the elongation and mechanical properties of the material.
Patent Information
- Application Number
- CN202410221572.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-02-28
AI Technical Summary
Due to thermodynamic incompatibility between polylactic acid and polybutylene succinate, the mechanical properties of the blend are insufficient. The existing capacity-enhancing methods have complicated synthesis, high cost, insufficient universality and complex operation. degree and other issues.
By introducing carbon black as the third component and combining Pickering emulsion template and melt blending technology, polylactic acid/polybutylene succinate@carbon black composite material was prepared, which significantly improved the compatibility of polymer blends. and mechanical properties.
Significantly improve the elongation of the break of polylactic acid/polybutylene succinate@carbon black composite material, reaching 230%, an increase of nearly 15 times, while improving the tensile strength and Young's modulus of the material, improving The comprehensive performance of the material.
Smart Images

Figure CN118005963B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer blend material preparation, and in particular relates to a method for improving the compatibility of incompatible polymer blends, which is used for improving the comprehensive performance of biodegradable polymer materials. Background Art
[0002] Plastics have an irreplaceable position in daily life and industrial applications due to their low cost, durability and lightness. However, the non-degradable nature of traditional plastics has led to serious environmental problems. Biodegradable plastics, such as polylactic acid, a polyester material made from lactic acid by polymerization, have high modulus, high strength, good biocompatibility, non-toxicity and sustainable production characteristics, and have been widely used in many fields. However, the application of polylactic acid is limited by its inherent brittleness.
[0003] In order to overcome this shortcoming, researchers have tried to blend polylactic acid with materials with different physicochemical properties, such as polycaprolactone, poly(butylene adipate-terephthalate), polyurethane, polybutylene succinate, etc. As a biodegradable material with good toughness, polybutylene succinate should exhibit excellent material properties when blended with polylactic acid. However, due to the thermodynamic incompatibility of polylactic acid and polybutylene succinate, improving the compatibility of the two has become a challenge. Traditional methods include physical and chemical compatibilization, which aims to promote compatibility by adding a third component or functional group small molecules. Despite the use of a variety of compatibilization strategies, existing technologies still fail to meet the expected goals in improving the performance of incompatible polymer blends. The current compatibilization methods face problems such as cumbersome synthesis and high cost of compatibilizers, lack of universality and high operational complexity, which not only limits its effectiveness in a wide range of application scenarios, but also increases the technical difficulty and cost of material processing. Therefore, the development of a new capacity-enhancing technology that can effectively improve the compatibility of polymer blends and is simple and easy to use is of great significance for optimizing the comprehensive properties of these materials, broadening their application scope, and promoting the progress of research and application of sustainable polymer materials. Summary of the invention
[0004] In order to overcome the problem of insufficient mechanical properties of polylactic acid / polybutylene succinate blends caused by thermodynamic incompatibility between polybutylene succinate and polylactic acid, the present invention provides an innovative new method for compatibilizing biodegradable polymer blends. The method performs compatibilization modification on polylactic acid and polybutylene succinate, two essentially incompatible polymers, and successfully prepares a biodegradable polymer composite material with significantly improved comprehensive properties, namely polylactic acid / polybutylene succinate@carbon black composite material, by using carbon black as an effective third component and combining Pickering emulsion template and melt blending technology.
[0005] The technical solution adopted by the present invention is: a method for increasing the volume of incompatible biodegradable polymer blends, comprising the following steps: step 1: mixing polybutylene succinate and carbon black through a Pickering emulsion template method to obtain a composite masterbatch; step 2: melt-blending the obtained composite masterbatch with polylactic acid to obtain a polylactic acid / polybutylene succinate@carbon black composite material.
[0006] Through a unique two-step composite technology, the present invention achieves an effective improvement in the incompatibility of the polymer polybutylene succinate and polylactic acid. Carbon black is introduced and coated on the surface of polybutylene succinate through the Pickering emulsion template technology to form a composite masterbatch. This composite masterbatch is then used as a dispersed phase and melt-blended with the matrix polylactic acid to prepare a structurally optimized polylactic acid / polybutylene succinate@carbon black composite material. The introduction of carbon black and the specific coating method significantly improve the compatibility of the polymer blend, while avoiding phase separation between the dispersed phase and the matrix, and greatly enhancing the mechanical properties of the composite material. Compared with the traditional melt blending method, the composite material prepared by this method has an elongation at break of up to 230%, which is nearly 15 times higher, showing extremely excellent mechanical properties and wider application prospects.
[0007] Preferably, the mass ratio of the raw materials polylactic acid, polybutylene succinate, and carbon black in the method is (90-60): (10-40): (0.5-3), more preferably 70: 30: (0.5-3), and more preferably 70: 30: 1. In order to further improve the compatibility of polylactic acid and polybutylene succinate, and significantly enhance the mechanical properties of polylactic acid / polybutylene succinate@carbon black composite materials, the present invention optimizes the amount of filler carbon black added on the basis of the two-step composite technology. The present invention ensures that the size of the dispersed phase in the obtained composite material is appropriate while avoiding the agglomeration of carbon black, and the interfacial compatibility with the matrix polymer is significantly improved by precisely controlling the amount of carbon black added. This optimization strategy enables the final composite material to exhibit good tensile strength and Young's modulus while maintaining a high elongation at break, proving the significant effect of the present invention in improving the mechanical properties of biodegradable polymer composites.
[0008] Preferably, the particle size of the carbon black is 30-45 nm. Here, the carbon black with a particle size of 30-45 nm as a filler can play a better reinforcing effect, so that the composite material has excellent mechanical properties.
[0009] Preferably, the step 1 comprises: dissolving polybutylene succinate in dichloromethane as an oil phase, dispersing carbon black in an aqueous solution as an aqueous phase, blending the oil phase and the aqueous phase by Pickering emulsion, and post-treating the blend to obtain a composite masterbatch. To ensure the optimal emulsion stability and masterbatch quality, the volume ratio of the oil phase to the aqueous phase is in the range of 1: (2.5-3.5), preferably 1: 3, and a homogenizer is used to homogenize at a speed of 10000-12000rpm for 2-3min. To obtain the composite masterbatch, the blend needs to be post-treated after Pickering emulsion blending. The post-treatment generally comprises: stirring the blend to volatilize dichloromethane, then filtering to remove water and drying to obtain a composite masterbatch. More specifically, the post-treatment includes: stirring the blend in a fume hood with a stirring paddle at a speed of 300-350 rpm for 20-24 hours, and after the dichloromethane is completely volatilized, removing water by filtration and drying in a 50-60° C. forced air oven for 20-24 hours.
[0010] Preferably, the step 2 comprises: melt blending the prepared composite masterbatch with polylactic acid in a torque rheometer at 160-180° C. and 40-60 r / min, and the melt blending time is 6-8 min.
[0011] The present invention also provides a polymer composite material prepared by the above method, wherein the polymer composite material has polylactic acid as a continuous phase and carbon black as a filler coated on the surface of polybutylene succinate as a dispersed phase. Preferably, the polymer composite material includes 0.5 to 3 parts by mass of carbon black, more preferably 1 part by mass, and this ratio has been proven to maximize the mechanical properties of the composite material.
[0012] Beneficial effects of the present invention: The innovation of the present invention is to use carbon black of a specific particle size as a filler, and optimize the microscopic morphology of the polylactic acid / polybutylene succinate@carbon black composite material by combining the two-step composite technology of Pickering emulsion mixing and melt blending, thereby achieving a significantly improved elongation at break (up to 230%, an increase of nearly 15 times) compared to the traditional melt blending method. In addition, the method is simple to operate, low in cost, does not require complex chemical synthesis steps, conforms to the preparation principle of environmental protection, and provides a new efficient and economical way to compatibilize incompatible biodegradable polymer blends. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a stress-strain comparison diagram of the composite materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1.
[0014] Figure 2It is a comparison chart of mechanical property parameters of the composite materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1.
[0015] Figure 3 It is the SEM picture of the composite material prepared in Examples 1 to 3 of the present invention and Comparative Example 1, to show the difference in their microstructures. DETAILED DESCRIPTION
[0016] The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, in the absence of conflict, the features in the following embodiments and embodiments can be combined with each other. In the embodiments of the present invention, the methods used are all conventional methods unless otherwise specified, and the reagents used can be obtained from commercial sources.
[0017] Embodiment 1:
[0018] This embodiment provides a method for preparing a polymer blend composite material, and a polymer blend composite material prepared by the method, namely, a polylactic acid / polybutylene succinate@carbon black composite material. The specific preparation method is as follows:
[0019] Pretreatment stage: Polybutylene succinate particles (Xinjiang Lanshan Tunhe Polyester Co., Ltd., brand TH801, density 1.25g / cm 3 , melting point 113 ° C, melt index 10-20 g / 10 min), carbon black powder (Xianfeng Nano, XF115, particle size 30-45 nm), polylactic acid (Nature Works, USA, brand 4032D, melt index 6.17 g / 10 min, density 1.24 g / cm 3 , melting point of 148-160°C, weight average molecular weight and number average molecular weight of 1.85×105 g / mol and 1.22×105 g / mol respectively) was dried in a forced air oven at 60°C for 12 h.
[0020] Step 1: 1 part by mass of carbon black powder is uniformly dispersed in the water phase, and 30 parts by mass of polybutylene succinate is dissolved in the dichloromethane solution to form an oil phase. These are mixed at an oil-water ratio of 1:3, and homogenized for 3 minutes at 12,000 rpm using a homogenizer to form a polybutylene succinate @ carbon black emulsion. The emulsion is stirred at 350 rpm in a fume hood for 24 hours to allow the dichloromethane to fully evaporate, and then filtered and dried in a 60°C blast oven for 24 hours to obtain a composite masterbatch.
[0021] Step 2: 70 parts by mass of polylactic acid are melt-blended with the above-mentioned fully dried composite masterbatch. The melt-blending conditions are: temperature 180° C., rotation speed 60 r / min, and blending time 8 min to obtain the final polylactic acid / polybutylene succinate@carbon black composite material.
[0022] The prepared polylactic acid / polybutylene succinate@carbon black composite material has a polylactic acid matrix as a continuous phase and 1 mass part of carbon black as a filler coated on the surface of polybutylene succinate as a dispersed phase.
[0023] Embodiment 2:
[0024] Compared with Example 1, Example 2 is different in that 0.5 parts by mass of carbon black is used in step 1, and the other steps are the same. The prepared polylactic acid / polybutylene succinate@carbon black composite material has a polylactic acid matrix as a continuous phase, and 0.5 parts by mass of carbon black as a filler coated on the surface of polybutylene succinate as a dispersed phase.
[0025] Embodiment 3:
[0026] Compared with Example 1, Example 3 is different in that 3 parts by mass of carbon black is used in step 1, and the other steps are the same. The prepared polylactic acid / polybutylene succinate@carbon black composite material has a polylactic acid matrix as a continuous phase, and 3 parts by mass of carbon black as a filler coated on the surface of polybutylene succinate as a dispersed phase.
[0027] Comparative Example 1:
[0028] Compared with Example 1, the difference of Comparative Example 1 is that no carbon black filler is added during the preparation process, and polylactic acid and polybutylene succinate are directly melt-blended to obtain a polylactic acid / polybutylene succinate binary blend. The specific preparation method is as follows:
[0029] Pretreatment stage: Polylactic acid powder (Nature Works, USA, brand 4032D, melt index 6.17g / 10min, density 1.24g / cm 3 , melting point of 148-160°C, weight average molecular weight and number average molecular weight of 1.85×105 g / mol and 1.22×105 g / mol respectively), polybutylene succinate particles (Xinjiang Lanshan Tunhe Polyester Co., Ltd., brand TH801, density 1.25 g / cm 3 , melting point 113°C, melt index 10-20g / 10min) was placed in a blast oven at 60°C and dried for 12h.
[0030] Step 1: melt-blending the fully dried polylactic acid and polybutylene succinate by means of a torque rheometer, the blending conditions being a temperature of 180° C., a rotation speed of 60 r / min, and a blending time of 8 min, to obtain a polylactic acid / polybutylene succinate blend.
[0031]
Performance test
[0032] The composite materials prepared in Examples 1 to 3 and Comparative Example 1 were subjected to mechanical property tests. The test method and test setting conditions were as follows: dumbbell-shaped specimens for mechanical property tests were made into dumbbell-shaped specimens by a universal specimen making machine, and stretched by a tensile testing machine at a stretching rate of 5 mm / min. The tensile test standard was based on GB / T 1040-2006. The test results are shown in FIG. Figure 1 , Figure 2 As shown. Figure 1 It can be seen that the elongation at break of the polylactic acid / polybutylene succinate@carbon black composite materials (Examples 1 to 3) obtained by two-step composite technology after the introduction of carbon black is better than that of the polylactic acid / polybutylene succinate blend provided in Comparative Example 1, among which the elongation at break of Example 1 is the highest. Comparing Example 1 with Comparative Example 1, the elongation at break of the composite material obtained in Example 1 is as high as 230%, which is nearly 15 times that of Comparative Example 1. Figure 2 It can be seen that, compared with Comparative Example 1, although the elongation at break of the composite material prepared in Example 1 is greatly improved, its tensile strength and Young's modulus are not greatly reduced, so the composite material prepared in Example 1 has the best mechanical properties.
[0033] The composite materials prepared in Examples 1 to 3 and Comparative Example 1 were subjected to detailed scanning tests using a scanning electron microscope (SEM). The relevant cross-sectional morphology results are shown in FIG. Figure 3 As shown. Analysis shows that the polylactic acid / polybutylene succinate blend obtained in Comparative Example 1 exhibits a larger dispersed phase size, and an obvious phase separation phenomenon is observed between the dispersed phase and the continuous phase matrix. In contrast, although the dispersed phase size of the composite material prepared in Example 2 is reduced, there are still relatively obvious cracks at the phase interface; the composite material prepared in Example 3 shows a transition to a co-continuous phase structure, but the appearance of carbon black agglomeration weakens its mechanical properties, which is inferior to the composite material prepared in Example 1. In comparison, the dispersed phase size of the composite material prepared in Example 1 is significantly reduced, and the interface between it and the continuous phase matrix is unclear, which illustrates the high compatibility and uniform distribution between the dispersed phase and the matrix. This optimized microstructure, especially the refinement of the dispersed phase and good interface fusion, is the key factor for the composite material to exhibit optimal mechanical properties.
[0034] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope of the present invention.
Claims
1. A method for increasing the compatibilization of incompatible biodegradable polymer blends, characterized in that: The steps include: Step 1: Mix polybutylene succinate and carbon black by Pickering emulsion template method to prepare composite masterbatch; Step 2: melt-blending the prepared composite masterbatch with polylactic acid to prepare a polylactic acid / polybutylene succinate@carbon black composite material.
2. The method according to claim 1, characterized in that In the method, the mass ratio of the raw materials polylactic acid, polybutylene succinate and carbon black is (90-60): (10-40): (0.5-3).
3. The method according to claim 2, characterized in that In the method, the mass ratio of the raw materials polylactic acid, polybutylene succinate and carbon black is 70:30:(0.5-3).
4. The method according to claim 3, characterized in that In the method, the mass ratio of the raw materials polylactic acid, polybutylene succinate and carbon black is 70:30:
1.
5. The method according to claim 1, characterized in that The particle size of the carbon black is 30 to 45 nm.
6. The method according to claim 1, characterized in that The step 1 comprises: dissolving polybutylene succinate in dichloromethane as an oil phase, dispersing carbon black in an aqueous solution as a water phase, blending the oil phase and the water phase by Pickering emulsion, and post-treating the blend to obtain a composite masterbatch.
7. The method according to claim 6, characterized in that The post-treatment comprises: stirring the blend to volatilize the dichloromethane, then filtering off water and drying to obtain a composite masterbatch.
8. A polymer composite material prepared by the method according to any one of claims 1 to 7.
9. The polymer composite material according to claim 8, characterized in that The polymer composite material uses polylactic acid as a continuous phase and carbon black as a filler coated on the surface of polybutylene succinate as a dispersed phase.
Citation Information
Patent Citations
Ramee / polylactic acid biological all-degradable composite material and preparation method thereof
CN102558796A
Modified polylactic acid / polycaprolactone composite material and preparation method thereof
CN102643523A